The Impact of Science, Environment, Technology, and Society (SETS) Learning Model Integrated with Google Earth on Spatial Thinking Ability in Senior High School - Ilda Safira; Alfi Sahrina; Dwiyono Hari Utomo; I Komang Astina (JAMBURA GEO EDUCATION JOURNAL, 2024)
Developing spatial thinking skills in students often poses a challenge for Geography teachers in Indonesia. The concept of spatial relationships in geography places spatial thinking as a distinct aspect of intelligence, enabling individuals to identify patterns and trends in spatial change. Therefore, appropriate models and strategies are needed to develop spatial thinking skills. This study aims to determine the effect of the Science, Environment, Technology and Society (SETS) learning model integrated with Google Earth on students' spatial thinking ability. This research is a quasi-experiment with posttest-only design nonequivalent groups that uses a quantitative approach with the inferential statistical method using the Independent sample t-test parametric test. The subjects of this study were randomly selected XI grade students from SMAN 10 Malang including, XI-C class as the experimental class and XI-D as the control class. The research instruments used are seven essay questions on spatial thinking ability. The data obtained will be analyzed using parametric statistics Independent sample t-test and obtained sig value. (2-tailed) 0.041. The mean value of the experimental class is greater (80.14) than the mean value of the control class (72.08). It can be concluded that the Science, Environment, Technology, and Society (SETS) model integrated with Google Earth affects students' spatial thinking ability on the material of Disaster and Environment class XI SMAN 10 Malang City. Another finding of this study is that three syntaxes are dominant in bringing up and developing students' spatial thinking ability, namely initiation, concept development formation, and concept application.